2020
DOI: 10.18502/ijrm.v13i9.7664
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose aspirin on the pregnancy rate in frozen-thawed embryo transfer cycles: A randomized clinical trial

Abstract: Background: The results of previous studies on the effect of low-dose aspirin in frozenthawed embryo transfer (FET) cycles are limited and controversial. Objective: To evaluate the effect of low-dose aspirin on the clinical pregnancy in the FET cycles. Materials and Methods: This study was performed as a randomized clinical trial from May 2018 to February 2019; 128 women who were candidates for the FET were randomly assigned to two groups receiving either 80 mg oral aspirin (n = 64) or no treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The artificial cycle is a process of simulating the action of the natural ovulation cycle hormone changes on the endometrium, thereby affecting the receptivity of the endometrium. Numerous studies have favored the use of natural cycles for endometrial preparation, concerning the safety of drugs for endometrial preparation and pregnancy rates [ 5 , 6 ]. However, it is worth noting that the artificial cycle can choose the best time for embryo transfer, with a low cancellation rate.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial cycle is a process of simulating the action of the natural ovulation cycle hormone changes on the endometrium, thereby affecting the receptivity of the endometrium. Numerous studies have favored the use of natural cycles for endometrial preparation, concerning the safety of drugs for endometrial preparation and pregnancy rates [ 5 , 6 ]. However, it is worth noting that the artificial cycle can choose the best time for embryo transfer, with a low cancellation rate.…”
Section: Introductionmentioning
confidence: 99%
“…In one previous randomized controlled clinical trial carried out by Davar et al . (12) , there was no statistically significant difference between the two groups (aspirin versus no therapy), and both the chemical and clinical pregnancy rates and the abortion rate were similar (12) . Madani et al (13) in reported that, in contrast to our findings, aspirin administration during ICSI cycles increased the rates of implantation, clinical pregnancy, and live births (12) .…”
Section: Discussionmentioning
confidence: 90%
“…(12) , there was no statistically significant difference between the two groups (aspirin versus no therapy), and both the chemical and clinical pregnancy rates and the abortion rate were similar (12) . Madani et al (13) in reported that, in contrast to our findings, aspirin administration during ICSI cycles increased the rates of implantation, clinical pregnancy, and live births (12) . In 2000, Hsieh and colleagues (14) found that taking aspirin increased the clinical pregnancy rate, but they select women with thin endometrium (14) .…”
Section: Discussionmentioning
confidence: 90%
“…The endometrial thickness was actually lower (8.64 ± 1.60 vs. 9.29 ± 1.70; P = 0.028) in patients who received aspirin in comparison to the control group. Chemical and clinical pregnancy rates were not different [29 ▪ ].…”
Section: Vitamins and Supplementsmentioning
confidence: 81%